Pertumbuhan Janin Dalam Kandungan: Pengamatan Dan Upaya Peningicatannya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRACT Intraurine growth retardation (IUGR) cause higher perinatal mortality and long term disability. The measurement of fundal height and weight gain and the roll-over test are simple methods of intrauterine growth monitoring. IUGR infants are best delivered in hospitals where optimal intra-partum and neonatal care can be given.